The 27 February 2022 Lop Nor earthquake: detectability, location, and discrimination - Gibbons, Steven J. (2022)
A seismic event with mb 4.8 (Mw 4.2) was detected close to the Chinese Lop Nor nuclear test site on 27 February 2022. Waveforms recorded at regional and far regional distances in central Asia indicate greater likeness with previous earthquakes in the region than with historical nuclear tests. We investigate signal-to-noise ratio (SNR) at regional and global stations, and find the best signals in central Asia and Alaska. Lower SNR at stations in China, Europe, and Australia is likely related to the radiation pattern. A joint probabilistic location of the 2022 event and well-constrained historical nuclear tests indicates an epicenter near 41.88° N and 88.10° E, about 25 km northwest of the tunnel portion of the test site. A moment tensor inversion using high-quality regional signals indicates a nearly deviatoric source with a 72% double couple and a reverse fault mechanism. The centroid depth is 20–25 km, consistent with depth phases recorded in Alaska. The observed faulting geometry and source composition for the 2022 Lop Nor event is consistent with previous earthquakes in the region and the spatial alignment of local geomorphological features, indicating tectonic and not anthropogenic origin.